Global opioid agonist treatment: a review of clinical practices by country. (19th May 2020) - Jin, Harry; Marshall, Brandon D. L.; Degenhardt, Louisa; Strang, John; Hickman, Matt; Fiellin, David A.; Ali, Robert; Bruneau, Julie; Larney, Sarah
ABSTRACT: Aims: We assessed how opioid agonist treatment (OAT) for opioid use disorder (OUD), specifically methadone and buprenorphine, including buprenorphine‐naloxone, is delivered in routine clinical practice, with a focus on factors that affect access to and delivery of these services. The aims of this review were to summarize eligibility criteria for entry to OAT, doses in routine clinical practice, access to and eligibility for unsupervised dosing and urine drug screening practices in OAT programs globally. Methods: We completed searches of PubMed, Embase, and grey literature databases for cross‐sectional or observational cohort studies of OAT using either methadone or buprenorphine. Dose data extracted from eligible studies were compared with guidelines provided by WHO. Results: We found 140 reports from 41 countries that contained data for at least one of the relevant indicators. A diagnosis of opioid dependence or opioid use disorder was the most common eligibility requirement for OAT (13 or 17 countries). Reported mean or median doses for methadone ranged from 16–131 mg whereas range for buprenorphine was 2.5–19 mg. Access to unsupervised dosing under some conditions was reported in 18 of 27 countries. Frequency of regular urine drug screenings (UDS) ranged from several times a week to eight times per year (methadone) or as clinically indicated. Conclusions: Opioid agonist treatment practices, including doses prescribed, vary greatly both within and across countries. Of particular concern is the persistence of lower dose prescribing practices, in which patients may be prescribed doses below those proven to yield significant clinical benefits.